Pelatihan Pembuatan Pakan Ikan Fermentasi Pada Kelompok Pembudidaya Ikan Nila (Oreochromis sp.) di Sangatta Selatan, Kutai Timur : Pelatihan Pembuatan Pakan Ikan Fermentasi Pada Kelompok Pembudidaya Ikan Nila (Oreochromis sp.) di Sangatta Selatan, Kutai Timur - Muhammad Hirwan Wahyudi; Eny Heriyati; Anshar Haryasakti Haryasakti; Yunca Muhimatul Hasanah (Universitas Muhammadiyah Palembang, 2025)
Sangatta Selatan Village is one of the village names in Sangatta Selatan District, East Kutai Regency. This village has a freshwater fish farming village fostered by the STIPER Kutai Timur Community Service (PKM) team. Training in making fermented fish feed is an activity that aims to provide skills to fish farmers and the community in Sangatta Selatan District. Providing fermented feed is one way that can be done to increase the growth of tilapia. Training in making fermented fish feed in this activity uses easily available materials, namely commercial feed, molasses and EM4 (effective microorganisms 4). This method was chosen because the process is quite simple and easy to practice, but has enormous benefits for saving production costs. This PKM activity is carried out by providing several theories regarding the methods and benefits of fermented feed which are continued with the practice of making it. The results of this activity are easy to implement by tilapia farmers and are recommended in tilapia cultivation for more optimal and efficient results so that they can save production costs.